Design and Performance Test of Squirrel Cage Hydrokinetic Turbine - Yin Yin Aye (AI Society & STMIK Indonesia, 2026)
This paper focuses on the design and performance test of squirrel cage hydrokinetic turbine. The design water flow velocity is 1.2 m/s and the designed water turbine has 3 blades. Turbine design is calculated by changing the aspect ratio. According to design calculation, maximum torque is found on aspect ratio 0.5. Squirrel cage hydrokinetic turbine is constructed by using the calculated design data. The turbine design diameter is 0.925m and height is 0.463 m. The turbine performance is tested at a canal near Mandalay Technological University. The experimental test results of rotational speed, angular velocity and turbine power for water velocity 1.2 m/s are 29 rpm, 3 rad/s and 68.2 W respectively. Moreover, theoretical and experimental test results of rotational speed, angular velocity and turbine power are compared by changing water velocity. According to the theoretical and experimental results, if the water velocity is increased, the rotational speed and turbine power are gradually increased. Keywords : aspect ratio, performance test, power, theoretical, water velocity